Changes on oxidative stress-related biomarkers in plasma and cardiac tissue due to prolonged exposure to normobaric hyperoxia - Maria Christina Dwiyanti; R Benettan; F Wandy; M Lirendra; Frans Ferdinal; David Limanan (Indonesian Society for Biochemistry and Molecular Biology, 2019)
Background: Hyperoxia is a state of oversupply of oxygen in tissues and organs that can increase reactive oxygen species (ROS). When antioxidants cannot balance ROS levels, oxidative stress occurs. Catalase and reduced glutathione (GSH) are two of the antioxidants that can be very useful to counteract ROS. Increased production of ROS subsequently results in lipids damage and generates malondialdehyde (MDA). ROS interaction with cardiac cells causes remodeling thus leads to heart failure. Objectives: The purpose of this study was to find out the changes on oxidative stress-related biomarkers in plasma and cardiac tissue. Methods: Sprague Dawley rats were divided into 5 groups (n=6/group). Control group was exposed to normoxia (21% O2), while each treatment group was exposed to hyperoxia (75% O2) for 1, 3, 7, and 14 days. Blood and heart samples were used for blood gas analysis and hematology test, also for catalase specific activity measurement, GSH level, and MDA level measurement. Results: Blood gas analysis of pO2, pCO2, and HCO3 were increased, while the O2 saturation and all hematological parameters were decreased. Plasma and cardiac tissue’s catalase specific activity increased in day 1 to day 7 but declined in day 14. Cardiac tissue’s GSH has the same result. Plasma GSH level increased in day 1 but decreased afterward. MDA level in plasma and cardiac tissue increased significantly since day 1. Conclusion: Hyperoxia causes oxidative stress, marked by the increase of oxidative stress-related markers, and partially compensated respiratory acidosis.